POTENSI EKSTRAK DAUN KERSEN SEBAGAI BAHAN SANITASI KERABANG TELUR PADA PROSES PENETASAN TELUR ITIK ALABIO: The Potential Of Cherry Leaf Extract (Mutinga calabura L) As A Sanitary Agent For Eggshell In The Alabio Ducks Hatching Process - Gilang Ayuningtyas; Rina Martini; Wina Yulianti (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2020)
The objective of this research was to study the potential of cherry leaf extract as natural sanitizer agent for Alabio eggshell in hatching process. A number of 533 of Alabio hatching eggs were used in this study. Hatching eggs produced from College of Vacational Studies IPB University, were collected three times a day. Three hundred thirty-three hatching eggs were divided into five treatment groups. The first group was considered as control, the second was dipping into commercial disinfection, and the third and the fifth gruop were dipping into cherry leaf extract 250 ppm, 500 ppm, and 750 ppm respectively. The results showed cherry leaf extract has secondary metabolite compounds : alkaloids, flavonoids and tannins. All of these secondary metabolite compounds have a role as antibacterial agent. cherry leaf extract 750 ppm shows the same potential as commercial disinfectants in reducing the microbial population in eggshells. The dipping treatment of 750 ppm cherry leaf extract in alabio duck hatching eggs resulted in the lowest embryo mortality rate compared to other treatments (9.3%). Key words: Alabio duck, cherry leaf extract, hatchery, total plate count of eggshell